0
$\begingroup$

We are given two independent random variables $X_1$ and $X_2$. We need to check whether $X_1$ and $X_1 X_2$ are independent or not.

Probability functions are given as : $P(X_i = -1) = P(X_i = 1) = \frac{1}{2}$ for $i=1,2$

Simply by looking at the random variables $X_1$ and $X_1 X_2$ can't we just conclude both are dependent, since the value of $X_1 X_2$ clearly depends on $X_1$ ? Or this isn't the way to proceed ?

$\endgroup$
2
$\begingroup$

Functional dependence and stochastic dependence are two different things. Think about a random variable $X$ which takes the values $1$ and $-1$ with probability $1/2$. Then $X^2=1$ which is constant, so $X$ is stochastically independent on $X^2$, even though they are functionally dependent. So the only way to check for stochastic independence in your example is to verify whether $$P(X_1=i,X_1X_2=j)=P(X_1=i)P(X_1X_2=j)$$ for $i,j\in\{-1,1\}$.

$\endgroup$
1
$\begingroup$

That's in general not the way to proceed. For example, if $X_3$ is a constant function, $X_3$ and $X_3$ are independent, so you cannot say just by looking at it, that $X_1$ and $X_1X_2$ are dependent. You have to look at the probiablities. We have \begin{align*} \def\P{\mathbf P}\P(X_1 = 1, X_1X_2 = 1) &= \P(X_1 = 1, X_2 = 1)\\ &= \P(X_1= 1) \P(X_2 = 1)\\ &= \frac 14 \end{align*} On the other hand \begin{align*} \P(X_1X_2 = 1) &= \P(X_1=1, X_2=1) + \P(X_1=-1, X_2=-1)\\ &= \frac 14 + \frac 14\\ &= \frac 12 \end{align*} So, $$\P(X_1 = 1, X_1X_2=1) = \P(X_1 = 1)\P(X_1X_2 = 1) $$ Along the same lines, we see that for any $i,j$: $$ \P(X_1 = (-1)^i, X_1X_2 = (-1)^j) = \P(X_1 = (-1)^i) \P(X_1X_2 = (-1)^j) $$ So, $X_1$ and $X_1X_2$ are independent.

$\endgroup$
1
$\begingroup$

It's a bit counterintuitive, but $X_1 X_2$ does not depend on $X_1$.

If $X_1=1$ and $P(X_2 = -1) = P(X_2 = 1) = \frac{1}{2}$, then

$P(X_1X_2 = -1) = P(1X_2 = -1) = P(X_2 = -1) = \frac{1}{2}$

In the same way, $P(X_1X_2 = 1)=\frac{1}{2}$

Second case:

If $X_1=-1$ and $P(X_2 = -1) = P(X_2 = 1) = \frac{1}{2}$, then

$P(X_1X_2 = -1)= P(-1X_2 = -1)= P(X_2 = 1) = \frac{1}{2}$

In the same way, $P(X_1X_2 = 1)=\frac{1}{2}$

So no matter what $X_1$ is, $P(X_1X_2 = -1)=P(X_1X_2 = 1)=\frac{1}{2}$

Intuitively, you could bescribe it as you being $X_1$ and picking $1$ or $-1$ at random and giving someone else ($X_2$) the possibility to negate what ou have chosen. As you can't know whether the other person will flip your choice, your pick and the result after the flip are independant.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.